2010
DOI: 10.1371/journal.pone.0010574
|View full text |Cite
|
Sign up to set email alerts
|

Cross-National Analysis of the Associations between Traumatic Events and Suicidal Behavior: Findings from the WHO World Mental Health Surveys

Abstract: BackgroundCommunity and clinical data have suggested there is an association between trauma exposure and suicidal behavior (i.e., suicide ideation, plans and attempts). However, few studies have assessed which traumas are uniquely predictive of: the first onset of suicidal behavior, the progression from suicide ideation to plans and attempts, or the persistence of each form of suicidal behavior over time. Moreover, few data are available on such associations in developing countries. The current study addresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
227
2
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 296 publications
(276 citation statements)
references
References 44 publications
41
227
2
6
Order By: Relevance
“…In a study of World Mental Health Survey data, of all traumatic events correlated with suicidal behavior (including SI), sexual violence was the most prominent (Stein et al, 2010). This also is consistent with a recent large-scale study of the relationship between gender-based violence and mental health in women.…”
Section: Discussionsupporting
confidence: 83%
“…In a study of World Mental Health Survey data, of all traumatic events correlated with suicidal behavior (including SI), sexual violence was the most prominent (Stein et al, 2010). This also is consistent with a recent large-scale study of the relationship between gender-based violence and mental health in women.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, studies have found strong associations between interpersonal trauma and suicidality, especially sexual trauma (Stein et al, 2010) and childhood trauma (Afifi et al, 2016; Dube et al, 2001). Among those who had experienced sexual trauma or childhood trauma in our study, we found an association with suicidality in both genders, which was stronger for men.…”
Section: Discussionmentioning
confidence: 90%
“…The risk of suicidality may also vary according to type of traumatic event. For example, a study based on the WHO’s mental health surveys implemented in 21 countries ( n  = 102,245) and investigating a range of traumatic events and suicidal behaviour (Stein et al, 2010) found that the strongest associations were found for violence-related events. In addition, previous studies have shown increased risk of suicidal behaviour subsequent to adverse and traumatic life events during childhood (Afifi et al, 2016; Bruffaerts et al, 2010), for both suicidal ideation (Stansfeld et al, 2017) and suicide attempts (Dube et al, 2001; Enns et al, 2006; Ford & Gomez, 2015).…”
mentioning
confidence: 99%
“…If both PTSD and depression were eliminated, a full 45% of past-year suicidality might be prevented. In a previous investigation of the association between traumatic events and suicidality, which involved 102,245 respondents (age 18 þ) from 21 countries participating in the WHO World Mental Health Surveys (Stein et al, 2010), PARP results suggested that 15.4% of all suicidal ideation and 22.1% of suicide attempts were attributable to traumatic events. In the only prior study to examine PARPs for both PTSD and depression in association with suicidality (Bolton and Robinson, 2010), results suggested that PTSD accounted for 6.3% of all suicide attempts, while 26.6% of all suicide attempts were attributable to depression.…”
Section: Comorbidity Of Ptsd and Depressionmentioning
confidence: 97%